Number 13 (October 1982) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1982)
Initial Changes in Fish Species Composition in Two Lakes of the Tennessee - Tombigbee Waterway, Alabama-Mississippi. By T.J. Timmons, 4 pp.
Keywords: fishes; tennessee; tombigbee waterway